Analysis of the strength of METAL ARC WELDING (SMAW) against bending tests in the WELD METAL area - Mochammad Rizal; Mochamad Mas'ud (CV. AFDIFAL MAJU BERKAH, 2025)
This study analyses the effect of electrical current variation on the strength of Shielded Metal Arc Welding (SMAW) joints in low-carbon steel. SMAW was chosen because of its flexibility and low cost, but the quality of the joint is highly dependent on process parameters, especially electrical current. This study aims to identify the optimal current to obtain maximum joint strength in the weld metal area. The research method used is quantitative with an experimental approach. Low-carbon steel specimens were welded using E7016 electrodes with current variations of 75 A, 80 A, 85 A, 90 A, 100 A, 105 A, 110 A, and 115 A. The research population and sample were low-carbon steel specimens with a V-groove joint design. The tests were conducted using the three-point bending test method to measure the maximum force, deflection, bending energy, and bending stress. The data were analysed numerically and presented in tables and graphs. The results showed that a current of 100 A produced the best strength, with the highest bending stress of 258.62 MPa and the highest bending energy of 4.94 J. These values indicate optimal ductility and strength. Current variations that were too low (below 100 A) or too high (above 100 A) resulted in a decrease in joint quality. Too low a current results in suboptimal penetration, while too high a current causes excessive heat and reduces ductility. In conclusion, selecting the right welding current, which is in the range of 100 A, is crucial for producing efficient and high-quality welds.